Performance Evaluation of IoT Middleware - Cruz, Mauro Alexandre Amaro da (2017)
The Internet of Things (IoT) is a term used to describe an environment where Billions of objects that are constrained in resources ("things") are connected to the Internet, and interacting autonomously. With so many objects interacting in IoT solutions, the environment in which they are inserted becomes smarter. A software called middleware plays a key role since it is responsible for most of the intelligence in IoT, acting as a "brain", integrating data from devices, allowing them to communicate, and make decisions based on collected data. Smart environments are heterogeneous by nature, considering the plethora of available technologies, and middleware can thrive, playing even a more relevant role in large scenarios, such as smart cities. This dissertation explores the requirements of IoT platforms, proposes a reference architecture model for IoT middleware, and details the best operation method of each proposed module. The document also proposes metrics, both qualitative and quantitative to evaluate middleware solutions objectively. Then, a performance evaluation study of open-source middleware solutions, as well as a proprietary solution developed by Inatel for the Inatel Smart Campus scenario. The results are analyzed and it is concluded that the proposed metrics are well adjusted for this type of solution and can play an important role when choosing the best solutions for a research work, as well as for real-life environments and industry. Sitewhere is the middleware solution that obtained better performance in the conducted study.